Marketing as a factor of the Croatian banking sector competitiveness - Rupčić, Nataša; Superina Gudelj, Irena (Oeconomica Jadertina, 2021)
Banking system represents a major part of the national  financial system. With its credit and investment activities, it enables national growth and development. With an increase in competition, the offer of banking services is becoming richer and more diversified. In this paper, banking system of the Republic of Croatia is analysed with the purpose of determining factors that could enhance the competitive advantage of banks. Key elements of the banking industry such as the number of banking companies, their size, concentration of the banking industry, entry barriers, investments in infrastructure and regulation of the market behaviour in the banking industry are analysed to assist the banks in making management decisions about their competitive position. Banking market is medium concentrated in the Republic of Croatia and there are substantial entry barriers in terms of capital requirements and business regulation. However, despite relatively intense competition, implicit agreements regarding determination of the capital price or interest margins based on the mutual monitoring of behaviour arenot possible due to a large number of substitutes from other financial institutions. For that reason, Nash equilibrium is determined by establishing low interest margins. That is why marketing, in terms of service marketing, can be determined as an important factor of banking behaviour and contributor to their competitive position.
Keywords: banking sector; concentration; competitiveness; service marketing; the Republic of Croatia